Family predictors of physical activity change during the COVID-19 lockdown in preschool children in Germany - Beck, Franziska; Schmidt, Steffen Christian Ekkehard; Woll, Alexander; Reimers, Anne Kerstin (Journal of Behavioral Medicine, 2022)
The COVID-19 pandemic is associated with crucial changes in children’s daily life including their physical activity (PA) and screen time (ST). Among preschool children, the family represents an important factor for sufficient PA levels by being the gatekeeper for PA. Thus, the aim of this study was to investigate the influence of the family environment, specifically SES, parental support, and having siblings on COVID-19-related changes of PA and ST behavior in 317 (170 boys, 147 girls) German preschool children using longitudinal data. Our results indicate a decline in total amount of sports-related PA, an increase in outdoor play, as well as an increase in leisure ST in preschool children. The changes in total amount of PA differed between children with different levels of parental support as well as in dependence on having siblings. Furthermore, levels of outdoor play and ST in preschool children were influenced by environmental factors like having access to their own garden. We conclude that the family environment (parental support as well as physical environment) is highly relevant for PA and ST levels in preschool children. To provide every child with PA opportunities during potential future lockdowns, restriction policies should be adapted and parents need sophisticated information about the importance of their support and thus the PA levels of their children.<br